Attracting inward foreign direct investment: An analysis on e-government practices and ease of doing business among countries in the ASEAN region - Zulkifli Mohamed; Farah Aida Ahmad Nadzri; Shahzadah Fahed Qureshi; Ahmed Abdullah Saad Al-Dhubaibi; Johan Arifin; Nathrah Yacob (Contemporary Economics, 2020)
E-government involves the application of the latest innovations while providing the provision of efficient services in the government's management systems. Whereas, ease of doing business is an index by World Bank that shows the easiness of doing business in particular country. These two variables are investigated in our study as they may contribute to the inflows of Foreign Direct In- vestment in the economy. Additionally, the study also includes two control variables which are the contribution of private industry and public industry in the GDP. Prior studies related to the topic are discussed in this study to develop various hypotheses. To conduct effective research, 26-years of data from the ASEAN countries were collected. After applying various approaches and techniques including panel co-integration test and DOLS estimation for testing different variables and their respective data, first major hypothesis of the study related to the e-government was rejected. Yet, another hypothesis emerged, regarding the impact of control variables such as contribution of private sector in GDP and contribution of public sector in GDP.
Keywords: F38; H5; 330; E-government Practices; ease of doing business; foreign direct investment; ASEAN